A Unitary or Multiple Representations of Numerical Magnitude? – the Case of Structure in Symbolic and Non-Symbolic Quantities - Moeller, Korbinian; Klein, Elise; Nuerk, Hans-Christoph; Cohen Kadosh, Roi (Frontiers in Psychology, 2012)
Currently, there is a controversial debate on whether there is an abstract representation of number magnitude, multiple different ones or multiple different ones that project onto a unitary representation. The current study aimed at evaluating this issue by means of a magnitude comparison task involving Arabic numbers and structured as well as unstructured non-symbolic patterns of squares. In particular, we were interested whether a specific numerical effect, the unit-decade compatibility effect reflecting decomposed processing of tens and units complying with the place-value structure of the Arabic number system, is affected by input notation. Indeed, a reliable unit-decade compatibility effect was observed in the symbolic-digital notation condition but absent for unstructured non-symbolic notation. However, for structured non-symbolic notation a – albeit negative - compatibility effect was observed as well. Theses results are hard to reconcile with the notion of an abstract representation of number magnitude. Instead, our data support the existence of multiple representations of numerical magnitude. In addition, the current data indicate that it may not be only a question of symbolic vs. non-symbolic but also an issue of the structuring of the input notation. While unstructured non-symbolic quantities seemed to be processed holistically we found evidence suggesting at least partially decomposed processing not only for symbolic Arabic numbers but also for structured non-symbolic quantities.